Effects of Dietary Inclusion of a Saccharomyces cerevisiae Fermentation Product on Performance and Gut Characteristics of Male Turkeys to Market Weight - Firman , J.D.; Moore, D.; Broomhead, J.; McIntyre, D. (International Journal of Poultry Science, 2013)
An experiment was conducted to test the effects of different levels of a Saccharomyces cerevisiae fermentation product on the performance and gut characteristics of male turkeys to 18 weeks of age. Turkeys were housed in a 32 pen facility (800 birds) with eight replicates and three levels (0.0625, 0.125, 0.25%) of XPC (Diamond V Mills) compared to a negative control without XPC. Experimental parameters measured included: body weight, feed intake, feed conversion, mortality and gut parameters (villi height, crypt depth, gut section histopathology). Processing yield was measured at the conclusion of the trial. All other diets and husbandry practices were based on industry standards. Feed efficiency was significantly improved in the 15-18 week period at all treatment levels (2.64 vs. 2.76 feed: gain at 18 weeks). No other differences in performance parameters measured were observed. Pectoralis major yield was higher in all treatment groups (19.9% vs. 20.7%) when compared to controls. No statistical differences were seen in gut samples in terms of gut scores, villi height, or crypt depth. The data reported here indicates that supplementing the diet with XPC may have a positive effect on the feed efficiency and breast meat yield of tom turkeys but that further studies are needed to define this effect.